TINJAUAN HUKUM TERHADAP PERLINDUNGAN HAK MILIK ATAS TANAH DALAM HUKUM ADAT (STUDI KASUS DESA MANJALLING) KAB. BULUKUMBA - Ashabul Kahfi; Aulia Andika Rukman; Muhajir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
his study examines the protection of land ownership rights from the perspective of customary law in Manjalling Village, Bulukumba Regency, with a focus on resolving land disputes involving boundary conflicts, inheritance issues, and multiple claims. The purpose is to analyze the dispute resolution mechanisms under customary law, their alignment with positive law, and the effectiveness of the legal protection provided. The research employs a descriptive qualitative approach through observation, interviews, and documentation involving customary leaders, community figures, local government officials, and parties involved in disputes. The findings reveal that resolution through customary deliberation is effective in maintaining social harmony and remains the preferred choice of the community, despite challenges such as the absence of disputing parties and differences in perception. Customary law in this area is consistent with the 1960 Basic Agrarian Law (UUPA) and the 1945 Constitution, serving as a complement to national law. Strengthening collaboration between customary institutions, the community, and local government is necessary to enhance the legality and protection of ownership rights in the future.